2009
DOI: 10.4161/psb.4.1.7419
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondria in the response of arbuscular mycorrhizal fungi to strigolactones

Abstract: The plant signals strigolactones activate seed germination of the parasitic weeds (Striga and Orobanche), growth of arbuscular mycorrhizal (AM) fungi and have recently been described as a new class of plant hormones that inhibit shoot branching. In AM fungi, the synthetic strigolactone analogue GR24 rapidly stimulates mitochondrial metabolism (within minutes) and biogenesis (within one hour). New gene expression, more active nuclear division and cell proliferation occur later (within days). By using pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…By this, the response of pathogenic fungi differs from the response of symbiotic AM fungi. SLs have been found to stimulate hyphal growth of AM fungi, causing intense branching activity characterized by cell proliferation, amplification of nucleus number per mycelial length and expression of genes related to mitochondrial activity and increased respiration (Giovannetti et al 1996;Buée et al 2000;Besserer et al 2006Besserer et al , 2009. BF from carrot hairy-root cultures and the SL analogs GR24 and GR7 were active on the phylogenetically distant AM fungi, Gigaspora sp.…”
Section: Discussionmentioning
confidence: 99%
“…By this, the response of pathogenic fungi differs from the response of symbiotic AM fungi. SLs have been found to stimulate hyphal growth of AM fungi, causing intense branching activity characterized by cell proliferation, amplification of nucleus number per mycelial length and expression of genes related to mitochondrial activity and increased respiration (Giovannetti et al 1996;Buée et al 2000;Besserer et al 2006Besserer et al , 2009. BF from carrot hairy-root cultures and the SL analogs GR24 and GR7 were active on the phylogenetically distant AM fungi, Gigaspora sp.…”
Section: Discussionmentioning
confidence: 99%
“…13.2 ). The extensive work of Besserer et al ( 2006Besserer et al ( , 2008Besserer et al ( , 2009 later corroborated this fi nding. The extensive work of Besserer et al ( 2006Besserer et al ( , 2008Besserer et al ( , 2009 later corroborated this fi nding.…”
Section: Strigolactones: Evolving Role In Am Symbiosismentioning
confidence: 75%
“…These responses are conserved in AM fungi as R. irregularis and G. rosea both responded in the same way. It was shown that these responses are dependent on an NADH dehydrogenase as well as an alternative oxidase in the respiratory chain (Besserer et al, 2008, Besserer, Bécard, Roux, & Séjalon-Delmas, 2009). Both enzymes are involved in GR24 response, while germination relies on the second only.…”
Section: Spore Germination and Early Signal Perceptionmentioning
confidence: 99%